A highly-random hopping sequence for jamming-resilient channel rendezvous in distributed cognitive radio networks. Issue 96 (September 2020) - Yang, Bo
Abstract: Channel hopping (CH) is an effective technique to reach a rendezvous in cognitive radio networks (CRNs). However, the holistic requirements of asynchronous clocks, heterogeneous channels, symmetric roles and anonymous identifiers make it particularly challenging to achieve deterministic and fast rendezvous. Moreover, some existing regular CH algorithms are easy to be detected and blocked by adversarial jammers. To overcome these deficiencies, this paper designs a novel Parity and Binary CH (PBCH) algorithm in a highly-random manner to enhance the level of anti-jamming. The key idea behind PBCH is to convert a randomly selected parity channel into a carefully designed binary template. Whether secondary users (SUs) select the same parity channel or not, the interleaved zeros and ones naturally included in the adequate binary template can guide fast rendezvous undoubtedly. We analyze the theoretical maximum time-to-rendezvous and the anti-jamming capability by virtue of the Chinese remainder theorem and the information entropy, respectively. We also compare PBCH with the prevailing rendezvous algorithms through extensive simulations. Evaluation results reveal that PBCH yields superior rendezvous latencies even under moderate jammer attacks.